Investigation of hydrodynamic instability growth in copper. (December 2018) - Sternberger, Z.; Opachich, Y.; Wehrenberg, C.; Kraus, R.; Remington, B.; Alexander, N.; Randall, G.; Farrell, M.; Ravichandran, G.
Highlights: Performed sample recovery of hydrodynamic instability growth experiments in copper. Determined instability growth factor as a function of peak pressure in the sample. Inferred strength of the copper sample by comparing measured growth factor to simulations of the instability growth. Graphical abstract: Abstract: Hydrodynamic instability experiments allow access to material properties at strain rates above 10 5 s − 1 . Existing models of material strength are not extensively validated at these strain rates. Recovery instability experiments were developed for copper samples. In conjunction with simulations using the hydrocode CTH, these experiments constrain the strength of copper at strain rates near 10 7 s − 1, providing an alternative technique to validate material properties at these strain rates. Mesh sensitivity in the present simulations contributed large uncertainty to the strength inferred from recovery instability experiments.